Genetic identification of degraded and/or inhibited DNA samples. Issue 4 (3rd July 2016) - Bogas, V.; Carvalho, M.; Anjos, M.J.; Corte-Real, F.
Abstract : Genetic identification of degraded biological samples can be a challenge as a consequence of the presence of low template DNA and a high content of PCR inhibitors. The aim of this work was to determine the best combination of extraction protocols and amplification kits to obtain the maximum genetic information from biological samples in different fabrics, subjected to distinct environmental conditions. To accomplish this objective, bloodstains on different fabrics were made and forensic samples identical to those found at crime scenes were simulated. These blood samples were simultaneously subjected to different environmental conditions – water well, inside of a house, buried in three types of soil and on the soil surface in a forest, in different seasons during a maximum period of two years. Washes of the bloodstains with detergent and bleach were also carried out. The samples were then extracted, quantified and, according to their quantification, were amplified with different amplification kits. The AmpFℓSTR MiniFiler was efficient in complementing partial genetic profiles from samples in different environmental conditions, when extracted with Chelex and amplified with AmpFℓSTR Identifiler. The use of mini-STR are of major importance, because they allow adding more genetic information with degraded and/or inhibited samples.